Reverse electrodialysis with NH4HCO3-water systems for heat-to-power conversion. (15th October 2017) - Bevacqua, M.; Tamburini, A.; Papapetrou, M.; Cipollina, A.; Micale, G.; Piacentino, A.
Abstract: A Reverse ElectroDialysis Heat Engine (REDHE) system operating with "thermolytic" ammonium hydrogen-carbonate (NH4 HCO3 ) aqueous solutions as working fluids is studied. The engine is constituted by (i) a RED unit to produce electric power by mixing the solutions at different salinity and (ii) a thermally-driven regeneration unit including a stripping and an absorption column to restore the initial salinity gradient thus closing the cycle. In the present work only the RED unit and the stripping column are taken into account. In particular, a simplified integrated process model for the whole cycle was developed: it consists of (i) a lumped parameter model for the RED unit validated with experimental data and (ii) a model developed via a process simulator to assess the thermal duty of the stripping column. The effect of operating conditions as solution concentrations and velocities was investigated by a sensitivity analysis. Under the best conditions (among those investigated), a power density of about 9 W/m 2 of cell pair was predicted for the RED unit, and a maximum exergetic efficiency of about 22% was found for the whole cycle. A preliminary economic analysis of the process is also provided. Highlights: A Reverse ElectroDialysis Heat Engine was studied to convert waste heat into power. Solutions of water and the thermolytic ammonium bicarbonate were adopted. For the first time, a process model for the whole cycle was presented. The RED model was validated with experimental data and a good agreement was found. A sensitivity analysis was performed to recognize the best operating conditions.